Effects of Retinal Transcription Regulation After GB20 Needling Treatment in Retina With Optic Neuritis - Chen, Jie; Zhang, Li; Gan, Xiulun; Zhang, Rong; He, Yinjia; Lv, Qiuyi; Fu, Haonan; Liu, Xiaodong; Miao, Linqing (Frontiers in Integrative Neuroscience, 2020)
Optic neuritis (ON) is one of the most frequent symptoms of multiple sclerosis that results in progressive loss of axons and neurons. In clinical trials of Traditional Chinese Medicine, needling at GB20 acupoint has been widely used for the treatment of ocular diseases including ON. However, the molecular mechanisms of needling at this site are still unclear. In this study, we induced ON by immunization with MOG35-55 peptide and investigated the effects of needling treatment at GB20 acupoint on retina with ON. RNA sequencing of retinal transcriptome revealed that, among the 234 differentially expressed genes induced by ON, 100 genes were upregulated and 134 genes were downregulated by ON, while needling at GB20 acupoint specifically reversed the expression of 21 genes compared with control treatment at GV16 acupoint. Among the reversed genes, Nr4a3, Sncg, Uchl1 and Tppp3 were involved in axon development and regeneration, which were downregulated by ON, indicating the beneficial effect of needling at GB20. Further gene ontology enrichment analysis revealed that needling at GB20 affected Circadian rhythm of mouse with ON. Our study first reported that needling treatment after optic neuritis at GB20 acupoint regulated gene expression of retina and reversed the expression of downregulated axon development related genes. This study also demonstrated that GV16 was a perfect control treatment site for GB20 in animal study. Our study provided scientific basis for needling treatments at GB20 for ocular diseases.